Vessel co-option: a unique vascular-immune niche in liver cancer - Yang, Dan; Dang, Shumin; Wang, Zhiyi; Xie, Meng; Li, Xiuling; Ding, Xiangming (Frontiers in Oncology, 2024)
Tumor vasculature is pivotal in regulating tumor perfusion, immune cell infiltration, metastasis, and invasion. The vascular status of the tumor is intricately linked to its immune landscape and response to immunotherapy. Vessel co-option means that tumor tissue adeptly exploits pre-existing blood vessels in the para-carcinoma region to foster its growth rather than inducing angiogenesis. It emerges as a significant mechanism contributing to anti-angiogenic therapy resistance. Different from angiogenic tumors, vessel co-option presents a distinctive vascular-immune niche characterized by varying states and distribution of immune cells, including T-cells, tumor-associated macrophages, neutrophils, and hepatic stellate cells. This unique composition contributes to an immunosuppressive tumor microenvironment that is crucial in modulating the response to cancer immunotherapy. In this review, we systematically reviewed the evidence and molecular mechanisms of vessel co-option in liver cancer, while also exploring its implications for anti-angiogenic drug resistance and the immune microenvironment, to provide new ideas and clues for screening patients with liver cancer who are effective in immunotherapy.